YAP-Induced Endothelial-Mesenchymal Transition in Oral Submucous Fibrosis. (July 2019) - Li, J.; Yao, M.; Zhu, X.; Li, Q.; He, J.; Chen, L.; Wang, W.; Zhu, C.; Shen, T.; Cao, R.; Fang, C.
Oral submucous fibrosis (OSF) is a potentially malignant disorder. Current studies have shown that chewing areca nut is considered the main cause of OSF, and endothelial-mesenchymal transformation (EndMT) participates in the occurrence and development of the fibrotic lesion. However, the specific molecular mechanisms and treatments remain unclear. Here, we report the mechanism of arecoline-induced EndMT and the importance of this mechanism in OSF, and we also identify potential therapeutics for decreasing OSF incidence. We demonstrate the overexpression of Yes-associated protein (YAP) in human samples and that it was significantly associated with OSF pathologic stage. Arecoline activated YAP by increasing reactive oxygen species levels and inducing the PERK pathway (eukaryotic translation initiation factor 2 alpha kinase 3), resulting in the initiation of EndMT and leading to OSF. Verteporfin, a YAP–TEA domain pathway inhibitor, suppressed EndMT and decreased collagen accumulation, resulting in the alleviation of OSF in mice. These data indicate that arecoline regulates the activity of YAP and highlight an alternative method for treating OSF.